Brucella microti and Rodent-Borne Brucellosis: A Neglected Public Health Threat - Rudolf, Ivo; Kejíková, Romana; Kosoy, Michael; Hubálek, Zdeněk; Mravcová, Kristína; Šikutová, Silvie; Whatmore, Adrian M; Al Dahouk, Sascha (Zoonoses and public health, 2025)
Brucellosis is one of the most important zoonoses worldwide, primarily affecting livestock but also posing a serious threat to public health. The major Brucella species are known to cause a feverish disease in humans with various clinical signs. These classical Brucella species are (re-)emerging, but also novel strains and species, some of them transmitted from rodents, can be associated with human infections. As a result of our review on rodent-borne brucellosis, we emphasise the need for more comprehensive surveillance of Brucella and especially Brucella microti in rodent populations and call for further research targeting the ecological persistence of rodent-associated Brucella species in the environment, their epizootic role in wild rodents and their virulence and pathogenicity for wildlife.
Keywords: Brucellosis; zoonózy; Public Health; rodent; Brucella; Rodentia; zvířata; Humans; public health risk; hlodavci; zoonosis; veřejné zdravotnictví; Zoonoses; sapronosis; lidé; brucelóza; Animals